The Effect of Dividend Payout Ratio (DPR), Company Size, And Debt To Equity Ratio (DER) on Glamor Stock Return in Manufacturing Companies Listed on The Indonesia Stock Exchange for the 2010-2020 Period - Putri, Fentia Ramadhani; Kufepaksi, Mahatma (International Journal Of Education, Social Studies, And Management (IJESSM), 2023)
This study aims to examine the effect of the Dividend Payout Ratio (DPR) variable, firm size, Debt to Equity Ratio (DER) on the glamour stock return in manufacturing sector companies for the 2010-2020 period. The type of data used in this study is quantitative data. This research method is in the form of causal-comparative with data testing technique based on descriptive statistical tests, classical assumption tests, multiple linear regression tests and hypothesis testing. The sampling technique uses the saturated sampling technique metho in Non-Probability Sampling and produces 27 companies as research samples. Based on the analysis of this study it is known that the Dividend Payout Ratio (DPR) has a positive effect on the return of glamor stock as evidenced by the results of the regression test of 0.098 and the t test of 0.006. Firm size has a significant positive effect on glamor stock returns as evidenced by the results of the regression test of 2.542 and the t-test of 0.001. Debt to Equity Ratio (DER) has a significant negative effect on the return of glamor stock as evidenced by the results of the regression test of -0.161 and the t-test of 0.000.